Pengaruh Keaktifan Siswa dalam Mengikuti Program Gabungan Remaja Islam terhadap Komitmen Beragama Islam - Yenifa Nur Annisa Yenifa; Eko Surbiantoro Eko; Huriah Rachmah (UNISBA Press, 2023)
Abstract. Islamic Senior High School (ISHS) 1 Bandung City has an unresolved problem, namely the existence of juvenile delinquency who are members of the student community. On the other hand, the school has Islamic spiritual extracurricular activities which are superior in terms of the moral development of its members. Based on these problems, the formulation of the problem posed is: